Unraveling the interplay: financial inclusion's impact on growth, trade dynamics, and foreign investment – a comprehensive empirical study - Kushwah, S.V.; Siddiqui, A.A. (University of Jaffna, 2024)
Ceylon Electricity Board (CEB) seeks alternative financing through Public Private Partnerships (PPP) due to non-cost-reflective tariff losses and debt overhang, relying on maturity in critical success factors. Thus, the research examines the success factors of Public Private Partnerships in developing power generation infrastructures in Sri Lanka, using quantitative data from a questionnaire distributed to stakeholders in CEB. The data analysis tools of descriptive and inferential statistics were used to analyze the collected data. The economic viability of the project, credibility of government policies, legal and regulatory framework, equitable risk allocation, transparent and efficient procurement process, financial market, a strong and good private consortium, and political stability, were found as the main CSFs for the development of mega power plants. The study was concentrated on the public agency of CEB, for generalization investigation to be extended to private investors, practitioners, and policymakers in the power sector. Further, a comprehensive study on the exploration of CSF to attract private investors to PPP for the development of mega power plants in Sri Lanka would be most beneficial to the industry. The framework developed in this research would be the benchmark for identifying critical success factors for improvement in PPP projects in Sri Lanka.
Keywords: Ceylon electricity board; Critical success factors; Public-Private partnership; JEL Classification: H54, H57, G32.